Clinical Presentations and Outcomes Related to Tuberculosis in Children Younger Than 2 Years of Age in Catalonia - Soriano-Arandes, Antoni; Brugueras, Silvia; Rodríguez Chitiva, Alejandro; Noguera-Julian, Antoni; Orcau, Àngels; Martín-Nalda, Andrea; Millet, Joan P.; Vallmanya, Teresa; Méndez, Maria; Coll-Sibina, Maite; Mayol, Luis; Clopés, Asumpció; et al. (Frontiers in Pediatrics, 2019)
Introduction: Children younger than 2 years have an increased risk of complications associated with tuberculosis (TB) due to the immaturity of the innate and adaptive immune response. We aimed to identify TB clinical presentations and outcomes as well as risk factors for complications in this age group. Materials and Methods: Multicenter, retrospective, cross-sectional study of TB cases in children aged <2 years in Catalonia (2005-2013). Epidemiological and clinical data were collected from the hospital medical records. TB complications, sequelae included, were defined as any tissue damage generating functional or anatomical impairment after being diagnosed or after TB treatment being completed. Statistical analyses were based on bivariate chi-square and multivariate logistic regression, and it was carried out with Stata® version 13.1. Odds ratios (OR) and its 95% confidence intervals were calculated (CI). Results: A total of 134 patients were included, 50.7% were male, the median [IQR] age was 13[8-18] months, and 18.7% (25/134) showed TB-associated complications. Pulmonary TB was diagnosed in 94.0% (126/134) of children, and the most common complications were lobar collapse (6/126). TB meningitis was diagnosed in 14/134 (10.4%), and hydrocephalus and mental impairment occurred in 1 and 2 patients, respectively. Two patients with spinal TB developed vertebral destruction and paraplegia, respectively. Only one of the patients died. At multivariate level, tachypnea (OR=4.24; 95% CI 1.17-15.35) and meningeal (OR=52.21; 95% CI 10.05-271.2) or combined/extrapulmonary forms (OR=11.3; 95% CI 2.85-45.1) were associated with the development of TB complications. Discussion: TB complications are common in children under two years old. Extrapulmonary TB forms in this pediatric age remain a challenge and require prompt diagnosis and treatment in order to prevent them. The presence of tachypnea at the time of TB diagnosis is an independent associated factor to the development of TB complications in infants. This clinical sign should be closely monitored in patients in this age group. It is necessary to perform further studies in this age group in a prospective design in order to understand whether there are other factors associated to TB complications.